Ambipolar behavior of Te and its effect on the optical emission of ZnO:Te epitaxial thin film. Issue 8 (26th February 2015) - Sahu, R.; Dileep, K.; Negi, D. S.; Nagaraja, K. K.; Datta, R.
<x xml:space="preserve">Abstract</x> We present control over the ambipolar nature of Te in ZnO and the corresponding optical band gap in epitaxial thin film grown by pulsed laser deposition. Experimentally, the decrease in band gap is found to be strongly dependent on the Te concentration for TeO compared to TeZn. Emission at 3 eV for TeZn, irrespective of Te content is explained by first principle calculation considering Zn vacancy in the lattice. An experimental band bowing parameter of ∼7 eV is obtained for TeO and is in agreement with modified Becke–Johnson potential (mBJLDA) based theoretical calculation. The physical insight into the nature of band bowing is elucidated.